Nitric Oxide in Cerebral Vasospasm: Theories, Measurement, and Treatment - Michael Siuta; Scott L. Zuckerman; J. Mocco (Neurology Research International)
In recent decades, a large body of research has focused on the role of nitric oxide (NO) in the development of cerebral vasospasm (CV) following subarachnoid hemorrhage (SAH). Literature searches were therefore conducted regarding the role of NO in cerebral vasospasm, specifically focusing on NO donors, reactive nitrogen species, and peroxynitrite in manifestation of vasospasm. Based off the assessment of available evidence, two competing theories are reviewed regarding the role of NO in vasospasm. One school of thought describes a deficiency in NO due to scavenging by hemoglobin in the cisternal space, leading to an NO signaling deficit and vasospastic collapse. A second hypothesis focuses on the dysfunction of nitric oxide synthase, an enzyme that synthesizes NO, and subsequent generation of reactive nitrogen species. Both theories have strong experimental evidence behind them and hold promise for translation into clinical practice. Furthermore, NO donors show definitive promise for preventing vasospasm at the angiographic and clinical level. However, NO augmentation may also cause systemic hypotension and worsen vasospasm due to oxidative distress. Recent evidence indicates that targeting NOS dysfunction, for example, through erythropoietin or statin administration, also shows promise at preventing vasospasm and neurotoxicity. Ultimately, the role of NO in neurovascular disease is complex. Neither of these theories is mutually exclusive, and both should be considered for future research directions and treatment strategies.